(untitled) (Health Renaissance, 2015)
Background: The role of inflammation in the pathogenesis of acute coronary syndrome (ACS) is established, however use of inflammatory markers as predictors for future short-term cardiovascular events in patients of acute coronary syndrome. Objective: To assess whether inflammatory markers C-reactive protein (hs-CRP), total leucocyte count (TLC) and serum albumin can correlate with the diagnosis of ACS in patients with acute chest pain and to see whether these markers can be used to predict short-term cardiovascular events in patients of ACS. Methods: All Patients presenting within 12 hours of the onset of central non traumatic chest pain were enrolled and investigated, the diagnosis of ACS was made as per JACC 2004 guidelines for ST-elevation myocardial infarction, unstable angina and non-ST elevation myocardial infarction. All patients received routine institutional care and treatment as per diagnosis blinded to CRP, albumin, and total leucocyte count (TLC). The independent predictors of ACS and predictors of adverse events in 30 days was evaluated using multivariate analysis. Results: one forty nine patients of ≥ 18 years (88 male, 61 female) which were included in the study, the diagnosis of non-ischemic chest pain (NICP)were in 30 (20%) and ACS in 119 (80%) patients. TLC and hs-CRP levels were higher (11576±3083, 14.04±6.17) in patients with ACS compared to NICP (5596±1370, 2.39±1.55) with significant P-value (<0.001). Significantly high hs-CRP level (19.95±6.46), TLC (15630±3522) and low serum albumin (3.45±0.31) were there in patients in whom adverse cardiovascular events occurred. Conclusion: Leucocyte count and hs-CRP level are the independent predictors of ACS in patients presenting to the emergency department with chest pain suggestive of ACS. High hs-CRP, TLC, neutrophil count and low serum albumin, lymphocyte count are independent predictors of adverse short-term cardiovascular events. Health Renaissance 2014;12(2): pp: 99-105